Relationship Between Metabolic Syndrome and the Brazilian Workers’ Food Program in Male and Female Manufacturing Workers - Pereira GS (Dove Medical Press, 2020)
Gabriela Santana Pereira,1 Ingrid Wilza Leal Bezerra,2 Anissa Melo de Souza,1 Isabelle Cristina Clemente dos Santos,3 Vivian Nogueira Silbiger,4 Raiane Medeiros Costa,1 Karina Gomes Torres,1 Antonio Gouveia Oliveira1,5 1Post Graduation in Health Sciences, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Natal, RN, Brazil; 2Department of Nutrition, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Natal, RN, Brazil; 3Post Graduation in Pharmaceutical Sciences, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Natal, RN, Brazil; 4Department of Clinical and Toxicological Analyses, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Natal, RN, Brazil; 5Pharmacy Department, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Natal, RN, BrazilCorrespondence: Ingrid Wilza Leal BezerraDepartment of Nutrition, Centro de Ciências da Saúde, Universidade Federal do Rio Grande do Norte, Av Sen Salgado Filho 3000, Natal, RN 59078-970, BrazilTel +55 84 988 218 964Email ingrid.nutri@hotmail.comIntroduction: Several studies have reported increased cardiometabolic risk among workers assisted by food assistance public policies. The aim of this study was to estimate the prevalence of metabolic syndrome (MetS) and its individual components among manufacturing workers and their relationship to the Brazilian Workers’ Food Program (WFP).Methods: It was a prospective, cross-sectional, two-stage survey comparative of manufacturing workers from companies adherent and non-adherent to the WFP stratified by sector of activity and company size. The workers were interviewed in the workplace, and data on waist circumference (WC), blood pressure, and 12-hours fasting blood glucose (FBG), serum triglycerides (TG), and total and HDL-cholesterol were obtained. Mixed effects multilevel regression was used to compare WFP and non-WFP groups separately in each sex. All subjects gave written informed consent.Results: The survey included 332 workers from 16 WFP companies and 344 workers from 17 non-WFP companies. The general prevalence of MetS, according to IDF/AHA/NHLBI criteria, was high but not statistically different between sexes (39.8% in females versus 28.5% for males, p=0.16). Statistically significant differences were found between sexes in the prevalence of individual components: WC (77.8% in females versus 38.3% in males, p=0.002), TG (27.3% in females versus 40.8% in males, p=0.07), and HDL-C (52.2% in females versus 43.1% in males, p=0.05). Among males, MetS prevalence was significantly higher in the WFP group (33.0% versus 23.9%, p=0.008), and, in the individual components, the WFP group had higher prevalence of increased WC (47.0% versus 29.4%, p< 0.001) and elevated FBG (8.9% versus 6.3%, p< 0.001), as well as greater average levels of TG, HDL-C and FBG. Among female workers, no statistically significant differences between groups were observed in MetS prevalence and its individual components, but WFP female worker presented lower systolic and diastolic blood pressure.Conclusion: In a low-income population, male manufacturing workers participating in a food assistance program are at increased risk of MetS, an effect that was not identified among female workers.Keywords: public policy, workers, cardiovascular risk factors, metabolic syndrome, food insecurity